Increased aortic stiffness and elevated blood pressure in response to exercise in adult survivors of prematurity. Issue 12 (19th June 2020) - Barnard, Christopher R.; Peters, Matthew; Sindler, Amy L.; Farrell, Emily T.; Baker, Kim R.; Palta, Mari; Stauss, Harald M.; Dagle, John M.; Segar, Jeffrey; Pierce, Gary L.; Eldridge, Marlowe W.; Bates, Melissa L.
Abstract: Objectives: Adults born prematurely have an increased risk of early heart failure. The impact of prematurity on left and right ventricular function has been well documented, but little is known about the impact on the systemic vasculature. The goals of this study were to measure aortic stiffness and the blood pressure response to physiological stressors; in particular, normoxic and hypoxic exercise. Methods: Preterm participants ( n  = 10) were recruited from the Newborn Lung Project Cohort and matched with term‐born, age‐matched subjects ( n  = 12). Aortic pulse wave velocity was derived from the brachial arterial waveform and the heart rate and blood pressure responses to incremental exercise in normoxia (21% O2 ) or hypoxia (12% O2 ) were evaluated. Results: Aortic pulse wave velocity was higher in the preterm groups. Additionally, heart rate, systolic blood pressure, and pulse pressure were higher throughout the normoxic exercise bout, consistent with higher conduit artery stiffness. Hypoxic exercise caused a decline in diastolic pressure in this group, but not in term‐born controls. Conclusions: In this first report of the blood pressure response to exercise in adults born prematurely, we found exercise‐induced hypertension relative to a term‐born control group that is associated with increased large artery stiffness. These experiments performed in hypoxia reveal abnormalities in vascular function in adult survivors of prematurity that may further deteriorate as this population ages. Abstract : The long-term consequences of prematurity are not well understood. We found that adult survivors of prematurity have increased blood pressure during exercise and evidence of arterial stiffening.